High Tap Density Li4Ti5O12 Microspheres: Synthetic Conditions and Advanced Electrochemical Performance. Issue 9 (29th May 2017) - Ren, Jianxin; Ming, Hai; Jia, Zhenyong; Zhang, Yanqing; Ming, Jun; Zhou, Qun; Zheng, Junwei
Abstract: Preparation of uniform, spherical Li4 Ti5 O12 with high tap density is significant to achieve a high volumetric energy density in lithium‐ion batteries. Herein, Li4 Ti5 O12 microspheres with variable tap density and tunable size distribution were synthesized by a newly designed industrial spray‐drying approach. The slurry concentration, sintering time, sintering conditions after spraying, and the effect of lithium/titanium molar ratio on the lithium‐ion (Li + ) storage capability were investigated. A narrow particle size distribution of around 10 μm and a high tap density close to 1.4 g cm −3 of the Li4 Ti5 O12 spheres can be obtained under the optimized conditions. The Li4 Ti5 O12 spheres can deliver a much higher capacity of 168 mAh g −1 at a rate of 1 C and show a high capacity retention of 97.7 % over 400 cycles. The synthetic conditions are confirmed to be critical for improving the electron conductivity and Li + diffusivity by adjusting the crystal and spatial structures. As‐prepared high‐performance Li4 Ti5 O12 is an ideal electrode for lithium‐ion batteries or capacitors; meanwhile, the presented approach is also applicable for preparing other kind of spherical materials. Abstract : Batteries on tap : Spherical Li4 Ti5 O12 particles with high tap density and excellent electrochemical properties are synthesized based on a newly designed spray‐drying method. A detailed description of the synthetic conditions, resultant structure, and final lithium storage capability is given to design advanced electrode materials.